2014
DOI: 10.1093/glycob/cwu101
|View full text |Cite
|
Sign up to set email alerts
|

Glycobiology of leukocyte trafficking in inflammation

Abstract: To fulfill their potential, leukocytes must be able to exit the vasculature and reach the site of inflammation within the tissue. This process of leukocyte extravasation is a tightly regulated sequence of events that is governed by a host of cell adhesion molecules, cytokines, chemokines and lipid mediators. Of major importance to this process and the function of many of the proteins and lipids involved is the posttranslational modification of these moieties by glycosylation. The glycosylation process is coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 102 publications
0
44
0
Order By: Relevance
“…N-glycosylation is a major posttranslational modification of proteins that modulates folding, maturation, trafficking, and secretion, as well as specific protein functions (1)(2)(3). Contrary to many other posttranslational modifications, N-glycans are composed of many monosaccharide units, creating a large diversity of glycan structures (4,5).…”
mentioning
confidence: 99%
“…N-glycosylation is a major posttranslational modification of proteins that modulates folding, maturation, trafficking, and secretion, as well as specific protein functions (1)(2)(3). Contrary to many other posttranslational modifications, N-glycans are composed of many monosaccharide units, creating a large diversity of glycan structures (4,5).…”
mentioning
confidence: 99%
“…Sialyl Lewis X (sLe X ), for example, is a sialic‐acid‐containing tetrasaccharide epitope and is expressed on leukocytes. Binding of sLe X to selectins plays an important role in mediating leukocyte trafficking . Horstkorte et al.…”
Section: Mgl With Unreactive Functionalitiesmentioning
confidence: 99%
“…Studies have shown that Gal-1 inhibits functions of monocytes and macrophages [10], as well as migration of lymphocytes and neutrophils to inflammatory sites [11]. Gal-1 also has immunosuppressive effects.…”
Section: Introductionmentioning
confidence: 99%